Public Legitimacy of Management Dismissal Decisions in the Social Media Era: The Viral Case of “Anita Tumbler” - Afiah Mukhtar; Herenal Daeng Toto; Rahmat Rahmat; Masradin Masradin; Rif'ah Shafwah (LP2M IAIN Palopo, 2026)
This study aims to analyze how digital public reactions play a role in shaping the social legitimacy of management decisions to terminate employees in the social media era, using the viral case study of